Benthic-based contributions to climate change mitigation and adaptation. (27th January 2020) - Solan, Martin; Bennett, Elena M.; Mumby, Peter J.; Leyland, Julian; Godbold, Jasmin A.
Abstract : Innovative solutions to improve the condition and resilience of ecosystems are needed to address societal challenges and pave the way towards a climate-resilient future. Nature-based solutions offer the potential to protect, sustainably manage and restore natural or modified ecosystems while providing multiple other benefits for health, the economy, society and the environment. However, the implementation of nature-based solutions stems from a discourse that is almost exclusively derived from a terrestrial and urban context and assumes that risk reduction is resolved locally. We argue that this position ignores the importance of complex ecological interactions across a range of temporal and spatial scales and misses the substantive contribution from marine ecosystems, which are notably absent from most climate mitigation and adaptation strategies that extend beyond coastal disaster management. Here, we consider the potential of sediment-dwelling fauna and flora to inform and support nature-based solutions, and how the ecology of benthic environments can enhance adaptation plans. We illustrate our thesis with examples of practice that are generating, or have the potential to deliver, transformative change and discuss where further innovation might be applied. Finally, we take a reflective look at the realized and potential capacity of benthic-based solutions to contribute to adaptation plans and offer our perspectives on the suitability and shortcomings of past achievements and the prospective rewards from sensible prioritization of future research. This article is part of the theme issue 'Climate change and ecosystems: threats, opportunities and solutions'.